How bad are bananas? : the carbon footprint of everything - Berners-Lee, Mike (Profile Books, 2020)
Ten years on from first publication, a new edition of this invaluable and entertaining guide that shows just what effect everything has on carbon emissions, from a Google search to a plastic bag, from a flight to a volcano. How Bad Are Bananas? was a groundbreaking book when first published in 2009, when most of us were hearing the phrase 'carbon footprint' for the first time. Mike Berners-Lee set out to inform us what was important (aviation, heating, swimming pools) and what made very little difference (bananas, naturally packaged, are good!). This new edition updates all the figures (from data centres to hosting a World Cup) and introduces many areas that have become a regular part of modern life - Twitter, the Cloud, Bitcoin, electric bikes and cars, even space tourism. Berners-Lee runs a considered eye over each area and gives us the figures to manage and reduce our own carbon footprint, as well as to lobby our companies, businesses and government. His findings, presented in clear and even entertaining prose, are often surprising. And they are essential if we are to address climate change.